Influence of transaction costs on foreign exchange option contracts: intra-daily tests - Hoque, A.; Manzur, Meher; Poitras, G. (Bond University, Queensland, 2010)
This paper tests the impact of transaction cost specification on deviations from lower boundary and put-call parity properties. Using PHLX traded foreign exchange options, prices for puts and calls are matched to the nearest five minutes. The results indicate how boundaries on the arbitrage profit function determined by alternative measures of transactions costs can impact the interpretation of deviations from distribution free properties of options such as put-call parity.